PERSPECTIVES OF TRADITIONAL MARKET WOMEN ON EXCLUSIVE BREASTFEEDING IN THE WORKING AREA OF DELI TUA HEALTH CENTER WORK AREA YEAR 2023 - Yuki Nia Nadia Nahdeak; Ariani, Peny; Putri Ayu Yessy Ariescha (JURNAL KESMAS DAN GIZI (JKG), 2023)
Abstract One of the fundamental steps toward a healthy and productive life is breastfeeding, which is in line with the Sustainable Development Goals (SDGs) or Sustainable Development Goals 2030 (Bennett et al., 2020). Low rates of exclusive breastfeeding lead to various infant health problems. The North Sumatra Provincial Government has recorded 299 cases of infant mortality until July 2021. Records from the Ministry of Health of the Republic of Indonesia, as many as 31.36% of 37.94% of children are sick, because they do not receive exclusive breastfeeding. The prevalence of stunting in Indonesia is currently at 27.67%. The low coverage of exclusive breastfeeding is influenced by various obstacles to optimal breastfeeding, one of the biggest obstacles is working women, especially those who work in the informal sector. The purpose of this study was to determine "The perspective of women informal workers in exclusive breastfeeding in the working area of the Deli Tua Health Center. This research is a qualitative study with a descriptive phenomenological approach. The participants in this study were mothers of traditional market traders as many as 7 participants who were obtained using nonprobality sampling technique with purposive sampling type. The instrument used in this research is an interview guide. In collecting data, this study used the in-depth interview method to collect data. The location of this research is Deli Tua Tax in the working area of the Deli Tua Health Center. The results of the research conducted obtained the results of a description of the factors that influence the perspective of traditional market trader mothers in exclusive breastfeeding, namely knowledge, work, husband support and socio-culture.